Job Satisfaction and Evidence of Burnout Comparing Arab and Non-Arab Urologists with a Migration Background Working in German Hospitals - Matthias May (Thieme Medical and Scientific Publishers Pvt. Ltd., 2021)
Background In German hospitals, severe shortage of physicians can currently be partially compensated by hiring foreign physicians. Results on job satisfaction (JS) and physician burnout (PBO) in this important occupational group are currently not available. Methods The cross-sectional “Assessment of their urological work environment by foreign clinicians in Germany (EUTAKD)” study was conducted in 2020 using a 101-item questionnaire among physicians working in German urological departments who were born in a country outside Germany and having non-German citizenship. This study compared JS and the occurrence of PBO between Arab (group A, n = 57) and non-Arab (group B, n = 39) participants. Results Significant group differences with advantages for group B were analyzed in overall JS and also in other JS items. High scores in the PBO dimensions, that is, “emotional exhaustion” and “depersonalization,” were shown by 27.9 and 51.5% of the study participants, respectively, although there were no group differences found (p = 0.972 and 0.237, respectively). Conclusion Prospective longitudinal studies of appropriate intervention measures aimed at increasing JS and decreasing PBO are needed.